(untitled) (Bheshaja: Journal of Central Ayurveda Campus, 2025)
A right-sided sigmoid colon with excessively lengthy redundant loops and peculiar peritoneal relationship is an anatomical variation that mainly manifests as a developmental anomaly. It can result in a variety of acute and chronic clinical disorders. This study is a case report of variation in the position, orientation and length of sigmoid colon along with its redundant loop and peculiar fixation. A sigmoid colon with an abnormal length and position was discovered in a 45-year-old male cadaver at the Central Ayurveda Campus in Dang, Nepal, during an undergraduate student dissection session. In contrary to conventional length and course, the sigmoid colon was exceptionally long and traversed from the left iliac fossa, upwards, backwards and to the right to reach to the right upper lumbar region at the level of L3.The loop then descended downward to the right iliac fossa, from where it moved downward and medially into the pelvic cavity to join the rectum. Knowledge of such a rare variation is critical for interventional radiologists and colorectal surgeons. The findings of this study may be useful in informing surgeons and radiologists about different types of presentations of colon while performing an investigative or surgical procedure such as sigmoidoscopy, percutaneous cecostomy etc.